Functional differences among hamstring muscles in hip extension and knee flexion exercises - Yanagisawa, O. (Sports injuries and prevention, 2015)
The hamstring muscles consist of the long (BF-L) and short (BF-S) heads of the biceps femoris, semitendinosus (ST), and semimembranosus (SM). The BF-L, ST, and SM act on both hip extension and knee flexion as biarticular muscle, whereas the BF-S flexes the knee as a uniarticular muscle. The hamstrings are occasionally treated as a muscle group (hip extensors or knee flexors), but previous studies have reported morphological and functional differences among the hamstrings. The hamstrings show individual characteristics in architectural parameters (e.g. fiber length, pennation angle, and physiological cross-sectional area). These architectural differences are likely closely associated with differences in the force-generation capacity of each hamstring muscle. In addition, each muscle`s function is affected by the angle of the hip and/or knee joints. The morphology and function of one hamstring muscle cannot be considered representative of the whole muscle group and vice versa. Thus, treating the hamstrings as a single muscle unit by assuming a uniform inter-muscular architecture can result in an inaccurate account of hamstring muscle function.